A dual market structure design for the reform of an independent power grid system—The case of Taiwan. (November 2019) - Tsay, Ing-Sheng; Chen, Po-Han
Abstract: In 1988, when the idea of economic liberalism was spreading across nations, the United Kingdom opened an electricity market. Soon, to increase the operational efficiency, other countries followed suit and gradually induced free competition to the electricity market. The reform aims to liberalize electric power industry, mainly features a vertical integration and deconstruction of the electric power enterprises. This study researches the independent power grid system in Taiwan as an island, from the perspectives of the power industry and the general environment, including political and geographical factors. Difficulties faced in electricity industry reform are presented, followed by the proposition of a dual market structure and its execution plan. The dual market structure divides the whole power market into a household market and an industry and commerce market, with the hope of achieving better electricity pricing fairness and power utilization efficiency. After studying the electricity market conditions in Taiwan from three aspects, safety, price, and environmental protection, it is concluded that both the household market and the industry and commerce market can reach a balance for supply and demand. The policies on distribution of electricity generation sources could provide the household market with a stable electricity price as well as good investment incentives for the industry and commerce market. For environmental protection, the dual structure could facilitate regulation, and reduce the disruption over the competition of the industry and commerce market. Thus, the proposed structure is suitable for the reform for an independent power grid system.